Solar drying of agrocultural products - Catania, Peter (Avances en Energías Renovables y Medio Ambiente - AVERMA, 2023)
Research in agricultural applications of solar energy is receiving considerable attention in North América and in many other countries such as Italy and Brazil. This renewed interest stems from the fact that the prospects for growth is limited to the explotation and development of available energy resources. Additionally, the harnessing of solar energy is based on simple inexpensive technologies. This paper reviews the programmes on three fundamental designs, validation of simulation models and the research results of the drying of cereal grains with solar energy as applied in North América. The availability of construction material and the variation in the meteorological conditions will result in varied approaches. The conclusions reached in this study are: 1) Solar grain dryers cost in the range of 1.50 to 3.50 per square foot. 2) The rectangular shaped solar collectors built qith readily available materials are the mos efficient. 3) Solar drying is economically viable. 4) The practical problems associated with the portable, plástic reinforced designs integrated with low efficiencies, limits their usefulness, as a reliable solar collector. 5) Solar drying simulated models presented by Thompson and Bakker-Arkema are in reasonable agreement with experimental data.